Pengaruh Harga, Produk, Citra Merek, dan Layanan terhadap Kepuasan Konsumen di Cafe Kepiting Berserak Kotapinang - Riska Yani Harahap; Yuniman Zebua; Bhakti Helvi Rambe (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the influence of price (X1), product (X2), brand image (X3), and service (X4) on customer satisfaction (Y), both partially and simultaneously, at Cafe Kepiting Berserak Kotapinang. This research employs a survey method with a sample size of 96 respondents. The research instrument is a questionnaire, and the data is analyzed using multiple linear regression equations. The analysis results demonstrate that customer satisfaction is influenced by price, product, brand image, and service. However, other factors beyond these variables also affect customer satisfaction, which should be explored in future studies to enhance customer satisfaction from different perspectives.